A sampler on sampling - Williams, Bill (New York : Wiley, 1978)
The purpose of the book is to convey an understanding of the principles of statistical sampling to the non mathematically inclined person.
Includes index.
II 16/01/2019
Loans
Keywords: Sampling (Statistics)